Beberapa gejala disfungsi sendi temporomandibula pada anak: Penelitian pada murid SDN 2 Sengkang-Wajo Provinsi Sulawesi Selatan pada tahun 2011-2012 Some symptoms of temporomandibular joint on child: Research at SDN 2 SengkangWajo, Province South Sulawesi in 2011-2012 - Harun Achmad; Hendrastuti Handayani; Marhama F. Singgih (Journal of Dentomaxillofacial Science, 2013)
Temporomandibular joint (TMJ) has a very important role in the function of mastication, swallowing and talking.During the process of chewing, this joint sustains a large amount of stress. Some complex excessive pressure on thejoints can cause structural damage to the joints or interfere with the normal function of the relationship betweencondyle, discus and eminence that will result in pain and dysfunction. This study aimed to determine the frequencyrepresentation of TMJ dysfunction in 6-13 years-old children. Descriptive study was conducted by survey on studentsof SDN 2 Sengkang-Wajo totaling 297 children, consisting of 157 males and 140 females. The sampling using astratified random sampling, by means of sub-populations forming a relatively homogeneous state of the variables.Results showed that the frequency of TMJ dysfunction with symptoms of pain in the supporting muscles TMJ washigher (87.34%) compared to other symptoms, followed by symptoms of mouth opening limitation (62.02%), clicking(43.03%), deflection (21.51%), mouth opening deviation (16.45%), and crepitation (5.06%). Based on the prevalence,many students of SDN 2 Sengkang suffering from dysfunction TMJ with a variety of symptoms due to low levels ofdental and oral hygiene due to lack UKGS in school.